Estrategias metodológicas innovadoras utilizadas en la Unidad Educativa Grandes Genios para garantizar el aprendizaje significativo en el Nivel Inicial - Calvo Cevallos, Dolores Marivel (2022)
This research project is entitled "Innovative Methodological Strategies used in the Grandes Genios Educational Unit to guarantee meaningful learning at the initial level", which was developed with the aim of investigating efficient methodological strategies in teaching at the initial level through a diagnosis in the educational institution that is the object of study. For which the general objective is established to design innovative methodological strategies used by the teachers of the Grandes Genios Educational Unit, in the teaching-learning processes in children of the initial level to achieve meaningful learning; the methodology was based on descriptive and explanatory research with which the variables were described and the characteristics of the innovative methodological strategies and significant learning were produced; In the same way, the research was demonstrated with a mixed approach, since the information could be analyzed qualitatively and quantitatively, each response obtained in the application of the techniques of participant observation and the surveys applied to the 7 teachers and 23 parents. . To complement the research, the synthetic method and the hypothetical deductive method were used through which the reading of pictograms, the inclusion of themes in specific songs, the discovery and experimentation in the development of small projects, the construction of material innovative didactic tool to work with children, the tool for problem-based learning and collaborative learning.